Time-periodic Solutions to the Ginzburg-Landau-BBM Equations (Journal of Partial Differential Equations, 2001)
In this paper, the existence and uniqueness of the time-periodic solutions to the Ginzburg-Landau-BBM equations are proved by using a priori estimates and Leray-Schauder fixed point theorem.
Keywords: Time-periodic solution; a priori estimate; Leray-Schauder fixed point. theorem; Ginzburg-Landau-BBM equations